'A second Troy!' Nostos and the poetics of delirium and violence in Derek Walcott's Odyssey. Issue 1 (2nd January 2021) - Zargarzadeh, Haleh; Gabriel, Sharmani Patricia
ABSTRACT: Drawing principally from Édouard Glissant's conceptions of detour and délire verbal (verbal delirium) and Frantz Fanon's notion of the physical and psychological salience of violence, this article explores Odysseus' nostos, or homecoming, in Derek Walcott's re-envisioning of the Greek epic poem in The Odyssey: A Stage Version (1993). It examines the alienation experienced by Odysseus on his return to his homeland and the nature of his attempts to reorient himself with 'home'. It argues that violence and delirium serve as a poetics that helps Walcott's Odysseus reclaim home from the usurpation of the suitors and achieve nostos . It demonstrates how, through the errant figure of Odysseus and his circuitous journey homeward, Walcott turns the trope of nostos, with its emphasis on disguise and opacity, into a strategy that dismantles the fixed spatial and temporal boundaries between the Old World and the New, coloniser and colonised, putting Ithaca and Homer in dialogue with Walcott and the postcolonial Caribbean. It is hoped that the elucidation of Glissant and Fanon's ideas in the Ithacan context and quest for home will contribute to new conceptions of home and homecoming in Walcott's works and in Caribbean literature as a whole.